(Bio)ethics for all beings: a proposal under construction (Research, Society and Development, 2021)
(Bio)ethics for all beings is under construction as a theoretical framework – proposed by R. Siqueira-Batista – that has as its origin the ethics for all beings. It is based on fundamentals such as quiddity, totality, interdependence, and has its central principle in the laic compassion. It has applicability in bioethical conflicts involving end of life (euthanasia), environmental ethics and public health / Primary Health Care. This study was carried out based on articles on the (bio)ethics of all beings and aims to present the reflection about the nomenclature; to define the main foundations; and analyze its applicability. It was concluded that the (bio)ethics of all beings is a bioethical current that can be applied in different fields, as it defends a careful and affectionate look towards human and non-human beings, living and non-living.